Estratégias de gerenciamento pelo lado da demanda aplicadas aos consumidores de BT considerando a tarifa branca e a geração distribuída - Cunha, Murilo Vargas da (2016)
This Master s Dissertation presents a study on the technical and financial impact of the application of strategies for Demand-Side Management (DSM) in residential consumers BT (Group B), considering the white tariff and the inclusion of distributed generation (DG). The white tariff to be an hourly tariff enables the application of DSM strategies in the residential consumer. As DSM strategies were used load shifting and peak reduction, aimed at handling consumption at peak hours. Furthermore, DG was also considered as a DSM strategy. In this sense, the proposed methodology considers typical load curves ranged by consumption levels, DSM strategies, tariffs, natural resources, photovoltaic technology to GD and solar collector. As a simulation tool was used the Hybrid Optimization Model for Electric Renewables software (HOMER), which aims to analyze technical and economic implementation of DSM strategies, exploring the white tariff and the use of GD. The results showed that the combination strategies peak reduction and load shifting enable the use of the white tariff. The results showed that the combination of the load shifting and peak reduction strategies and enable the use of the white tariff. Already the use of DG due to maintenance and operating costs, required a sensitivity analysis observing at cost reduction.